CMMSE‐2019: Simulation and visualization of vehicular traffic on road networks using high‐performance computing systems. Issue 3 (13th March 2020) - Churbanova, Natalia; Chechina, Antonina; Trapeznikova, Marina; Ermakov, Aleksey; German, Mikhail; Sokolov, Pavel; Bozorov, Obidzhon
Abstract : The main object of this work is the vehicular traffic simulation based on macroscopic as well as microscopic approaches. First of them is one‐dimensional and uses the quasi‐gas‐dynamic system of equations. The second one simulates the multilane movement using the cellular automata theory. Different types of driver behavior are employed in the model. The self‐dependent problem is to apply the created software to the high‐performance computer systems to simulate the traffic flow on the real city network.